Junduqing extractive promotes the apoptosis of nasopharyngeal carcinoma cells through down-regulating Mcl-1 and Bcl-xL and up-regulating Caspase-3, Caspase-8 and Caspase-9. Issue 1 (4th December 2019) - Zhao, Weiguo; Tang, Lei; Gao, Shan; Xin, Ling; Zhang, Haiyong; Li, Yunjing
Abstract: This study aimed to investigate the effect of Junduqing extractive on proliferation, apoptosis, migration and invasion of nasopharyngeal carcinoma (NPC) cells and the involved mechanism. Junduqing extractive was prepared. CCK-8 assay found that IC50 of Junduqing extractive in HNE-1 cells was 2.99 mg/ml, so its concentration of 1.0, 2.0 and 3.0 mg/ml was selected to perform the following experiments. HNE-1, HNE-2 and HONE1 cells were then divided into four groups: (1) Control (no treatment); (2) 1.0 mg/ml (1.0 mg/ml Junduqing); (3) 2.0 mg/ml (2.0 mg/ml Junduqing) and (4) 3.0 mg/ml (3.0 mg/ml Junduqing). Cell viability, apoptosis, migration and invasion were examined by CCK-8 assay, annexin V-FITC/PI staining, scratch wound assay and transwell assay, respectively. Compared with the control group, the viability, migration rates and invasive capacity of HNE-1, HNE-2 and HONE1 cells with Junduqing treatments decreased significantly. Higher concentration of Junduqing extractive caused lower viability, smaller migration rates and weaker invasive capacity. Compared with the control group, the apoptosis of HNE-1, HNE-2 and HONE1 cells after treatment with 2.0 and 3.0 mg/ml of Junduqing extractive increased remarkably. Levels of Bcl-xL, Mcl-1, Caspase-3, Caspase-8 and Caspase-9 were examined by western blotting. Compared with the control group, the expression of Bcl-xL and Mcl-1 and the expression of Caspase-3, Caspase-8 and Caspase-9 in HNE-1, HNE-2 and HONE1 cells were significantly down-regulated and up-regulated, respectively, after treatment with Junduqing extractive. In conclusion, Junduqing extractive could inhibit the proliferation, migration and invasion, and promote the apoptosis of human NPC cells through down-regulating Mcl-1 and Bcl-xL and up-regulating Caspase-3, Caspase-8 and Caspase-9.